KESIAPAN GURU GEOGRAFI DALAM PELAKSANAAN PEMBELAJARAN DARING DI MAN 2 PADANG - Salsadila Avron; Yurni Suasti (JURNAL BUANA, 2021)
The objectives of this study were (1) To determine the readiness of teachers in using online learning applications in MAN 2 Padang. (2) To describe the readiness of geography teachers in preparing online learning materials at MAN 2 Padang. (3) To describe the readiness of the geography teacher in preparing online assignments at MAN 2 Padang. This research was conducted using a descriptive method with a qualitative approach and literature study with the research subject, namely the geography subject teacher at MAN 2 Padang, which consisted of 4 geography subject teachers. In collecting data, it is done by means of observation, interview and documentation study. The data analysis technique was referenced from the thoughts of Miles and Huberman, namely data reduction, data presentation, drawing conclusions / verification. The results of this study are: (1) The readiness of the teacher in using online learning applications, namely the use of WhatsApp and Google Classroom applications. This is because the WhatsApp and Google Classroom applications have more effective and easy-to-use features for geography teachers at MAN 2 Padang. (2) Teachers' readiness in preparing online learning materials through collaboration with colleagues at the MGMP and teaching materials from RPP that match the material to be discussed. (3) Teachers' readiness in preparing online learning assignments, namely geography teachers have readiness such as designing LKPD and also from student worksheets via WhatsApp group chat.